The Direct and Indirect Expropriation in International Investment Arbitration: The Peruvian Experience - Puccio, Ricardo (2025)
This article intends to explain, from the Peruvian experience, when we are facing a measure of direct or indirect expropriation under the scope of international investment law, and how these measures have been considered in international instruments designed to protect investments and in the relevant jurisprudence.